2018
DOI: 10.1177/1538192718795256
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of Chicana Feminism on College Success: A Literature Review

Abstract: Chicanas and Latinas are still severely underrepresented in higher education. Much of the previous literature focuses on the barriers to their success. This article highlights studies related to Chicana Feminism and the ways this perspective can positively impact college attainment and success. The authors conclude by discussing implications of biculturalism and further recommendations developing biculturalism among Chicanas and Latinas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Moreover, there are recent rich histories detailing the influences of Latinas in the feminist movement (Delgado-Romero et al, 2023; Manosalvas et al, 2023). Therefore, highlighting this work is crucial to make Latina feminism more visible and operating from a strengths-based perspective shifts the narrative from a deficit model and is congruent with multicultural approaches to psychology (Carrillo & Dean, 2020).…”
Section: Latina Feminismmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there are recent rich histories detailing the influences of Latinas in the feminist movement (Delgado-Romero et al, 2023; Manosalvas et al, 2023). Therefore, highlighting this work is crucial to make Latina feminism more visible and operating from a strengths-based perspective shifts the narrative from a deficit model and is congruent with multicultural approaches to psychology (Carrillo & Dean, 2020).…”
Section: Latina Feminismmentioning
confidence: 99%
“…As of 2019, the psychology workforce is less diverse than the U.S. population with Latinx psychologists making up 7% of the psychology workforce as compared to 18% of the U.S. population (American Psychological Association, 2020). The low numbers and heavy workload potentially limit the availability of Latinx faculty to serve as role models for the recruitment, retention, and graduation of Latinx students (Carrillo & Dean, 2020; Gloria & Robinson Kurpius, 1996).…”
Section: Latina Feminismmentioning
confidence: 99%
“…Today, Chicanas remain underrepresented in undergraduate and graduate education underscoring the significant problem of college access and completion still acute for this population (Carrillo & Dean, 2020;Pérez Huber et al, 2015). Most of the research conducted on what contributes to the academic success of Chicanas is found in K-12 contexts (S. Auerbach, 2004;Delgado Bernal et al, 2006;Delgado-Gaitan, 1994).…”
Section: Chicanas and Higher Educationmentioning
confidence: 99%
“…Within higher education, prior literature on Latina students in STEM has demonstrated the importance of STEM identity formation (Rodriguez et al, 2017), having a strong network of support from peers and faculty of the same race/ethnicity (Contreras Aguirre et al, 2020), and interventions that used collectivism and increased self-efficacy to improve department climate (Rincón & George-Jackson, 2016). And, while there have been continued calls and examples within educational research that utilize Chicana feminist epistemologies to better understand the experiences of Latina students within school and college settings, this scholarship remains limited (Calderón et al, 2012; Carrillo & Dean, 2020; Delgado Bernal, 1998).…”
mentioning
confidence: 99%
“…Like others having or living in more than one culture, we get multiple, often opposing messages. The coming together of two self-consistent but habitually incomparable frames of reference causes un choque, a cultural collision (p.85).” Chicana feminist perspectives, like Anzaldua’s, provide a lens to understand the unique experiences of Mexican-origin students by deconstructing concepts of gender and race as well as that of immigration, language, and religion (Calderón et al, 2012; Carrillo & Dean, 2020).…”
mentioning
confidence: 99%